METHODOLOGY FOR THE MULTI-CRITERIA EFFICIENCY ASSESSMENT OF CARGO CUSTOMS COMPLEXES (World Science, 2021)
Operation efficiency assessment of cargo customs complexes located throughout Ukraine and having different technical, technological and organizational support levels can be made based on various technical and economic performance indicatorsThe paper develops the methodology for a comprehensive efficiency assessment of customs infrastructure facilities as an integral system of local measures and system performance indicators as a whole. Forming the integral criterion and the generalized integral criterion, we take into account the parameters of the benchmark cargo customs complex.The developed methodology for multi-criteria efficiency assessment of customs infrastructure facilities makes it possible to identify the groups of technical and economic performance indicators, to rank the technical and economic performance indicators according to the significance of their influence on the final generalized efficiency indicator; to form a vector with the parameters of the benchmark cargo customs complex; to determine the generalized efficiency assessment indicator of a cargo customs complex according to each group of factors; to determine the integral and generalized integral indicator of the operation of a cargo customs complex